Joint discrete approximation of a pair of analytic functions by periodic zeta-functions - Balčiūnas, Aidas; Garbaliauskienė, Virginija; Karaliūnaitė, Julija; Macaitienė, Renata; Petuškinaitė, Jurgita; Rimkevičienė, Audronė (Mathematical Modelling and Analysis, 2020)
In the paper, the problem of simultaneous approximation of a pair of analytic functions by a pair of discrete shifts of the periodic and periodic Hurwitz zeta-function is considered. The above shifts are deﬁned by using the sequence of imaginary parts of non-trivial zeros of the Riemann zeta-function. For the proof of approximation theorems, a weak form of the Montgomery pair correlation conjecture is applied.